Natural selection at work? Vitamin D deficiency rates and rising health problems in young Turkish Cypriot professionals - Kandemiş, Emine; Tuncel, Gülten; Fahrioğlu, Umut; Temel, Şehime Gülsün; Mocan, Gamze; Ergören, Mahmut Çerkez (Central European Journal of Public Health, 2021)
OBJECTIVES: Vitamin D is a fat-soluble, prohormone vitamin that is important especially for bone mineralization and skeletal health. In recent years, vitamin D deficiency appeared as a worldwide problem, affecting many people in different ways including the Northern Cypriot population. The deficiency might be caused by the lack of exposure to sunlight, diet low in vitamin D, sedentary lifestyle, and also due to some genetic variations in the vitamin D receptor (VDR) gene. METHODS: In this study, four common VDR polymorphisms and associations with vitamin D deficiency in the Turkish Cypriot population between ages 18-40 and working in office conditions was studied by PCR- RFLP analysis. RESULTS: rs2228570 C>T variant was shown to be significantly associated with low serum vitamin D levels in the studied population. CONCLUSION: Together with the effect of rs2228570 C>T variant in the VDR gene, it is thought that the lifestyle changes in the Turkish Cypriot population might have caused the increased frequency of vitamin D deficiency in the young professionals.
Keywords: vitamin D; genetická predispozice k nemoci; Humans; polymorfismus délky restrikčních fragmentů; Polymorphism, Restriction Fragment Length; Genotype; Genetic Predisposition to Disease; Polymorphism, Single Nucleotide; lidé; jednonukleotidový polymorfismus; Vitamin D; mladiství; Young Adult; Vitamin D Deficiency; studie případů a kontrol; nedostatek vitaminu D; Case-Control Studies; genotyp; Adolescent; Selection, Genetic; mladý dospělý; dospělí; Adult; selekce (genetika)